HUBUNGAN ANTARA ANGKA KECACINGAN DENGAN STATUS PENGUKURAN ANTROPOMETRI ANAK USIA SEKOLAH DASAR DI KECAMATAN PEMENANG KABUPATEN LOMBOK UTARA NUSA TENGGARA BARAT - Gusti Anom Christyandi Ramarantika; Rifana Cholidah; Eva Triani (Unram Medical Journal, 2022)
Background: There are more than 1,5 billion cases of STH infections each year, with school-age children being the most susceptible demographic. Those infections could cause many health problems, some of which are nutrition related health problems. This study aims to learn about the correlation between helminth infection and anthropometry measurement of elementary school age children in Pemenang sub-district, North Lombok district, West Nusa Tenggara province. Method: This study uses correlation analysis with two categoric variables and consecutive sampling method. Helminth infections was checked trough feces sample examination. This study was carried out on SDN 1, S SDN 2, dan SDN 3 Malaka between May and December of 2019. Results: Helminth eggs was found on 23 samples (30,67%) from the total of 75 samples, with T.trichiura being the most frequent infections found (91,4%). Using Mann-Whitney test, it was found that there are no significant correlations between helminth infections and anthropometry measurement using height-for-age and weight-for-age indicators (p=0,814 & p=0,403), but there is a significant correlation between helminth infections and anthropometrical measurement using BMI-for-age indicators (p=0,025). Conclusion: There are no significant correlations between helminth infections and nutritional status that were assessed using height-for-age and weight-for-age indicators, but there is a significant correlation between helminth infections and nutritional status that was assessed using BMI-for-age indicator.